Efektivitas Dry Needling Dengan Ultrasound Terhadap Penurunan Nyeri Pada Kasus Myofascial Trigger Point Syndrome Otot Upper Trapezius - Theresita Kurniawati; Fransisca Xaveria Hargiani; Amin Zakaria; Yohanes Deo Fau (Jurnal Keperawatan Muhammadiyah, 2023)
To compare the effectiveness of dry needling with ultrasound to reduce pain in cases of myofascial trigger point syndrome of the upper trapezius muscle.Â